Problem of formation of pension capital in the Russian Federation - K. Gabdrakhmanov, Niyaz (2018)
The paper is devoted to the problem of pension capital formation in the country's financial system, which is topical for many countries. Pension provision plays an important role for social sustainability in any country. In the most developed countries, there are problems of reducing pension assets associated with population aging and a decrease in quantity of the working-age population. However, despite this, the developed countries of the world are trying to provide citizens with pensions at the proper level. Based on the analysis of the experience of foreign countries, it was concluded that it is necessary to increase pensions in the Russian Federation, taking into account several factors such as increasing in the assets of pension funds, increasing in pensions for current pensioners, fixing the retirement age for men and increasing it for women to ensure social justice at the level of developed countries. The paper also discusses the problems of the pension capital formation in the Russian pension system, which is more based on state pension provision for citizens and for many years has already experienced serious problems with the availability of funds to cover pension liabilities. The authors proposed a scientific and practical substantiation of the directions for increasing the effectiveness of the pension capital formation in the economy of the Russian Federation.